Tennessee and China: The Challenges and Opportunities of a Growing Trade Relationship - Georgia Varlan (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
In 2007, the state of Tennessee opened a trade office in Beijing to facilitate increased trade and investment between Tennessee and China, which has already grown by over 1,000 percent in the past five years. This paper begins by tracing a brief history of U.S.-China trade and economic relations, focusing on the period from the 1978 economic reforms to the present, as well as looking at some of the issues affecting U.S.-based entities exporting to China. Tennessee’s trade relationship with China is analyzed within this context, focusing on Tennessee exports to China and using both state trade data and case studies of Tennessee companies doing business in China. This data is then compared to trade data from the twelve states that have a higher dollar amount of exports to China per year than Tennessee. The paper concludes by looking at what overarching conclusions can be drawn about states successfully exporting to and investing in China and makes recommendations on how Tennessee’s state government and The Tennessee-China Development Center (Tennessee’s trade office in Beijing) can grow Tennessee’s overall trade volume with China and assist individual Tennessee businesses in trading with and investing in the Chinese market.
Keywords: Undergraduate Research; Pursuit